The Effect of Corporate Governance on the Financial Performance of State-Owned Enterprises Moderated by The Inflation Rate - Situmorang, Herman; Muchtar, Susy (Universitas Negeri Surabaya, 2024)
This study aims to analyze the effect of corporate governance on the financial performance of State-Owned Enterprises (SOEs) with the variable of the Inflation rate which is considered to moderate the relationship between corporate governance and SOEs financial performance. This study uses secondary data from the financial and annual reports of SOEs listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The purposive sampling method was used to collect 23 samples from the company. Analysis of hypothesis testing data using the E-views 9 application. The results of the study indicate that corporate governance proxied by Government Ownership, Institutional Ownership, Board of Directors Size, Independent Board of Commissioners Size has a negative and significant effect on SOEs financial performance as measured by ROA, conversely corporate governance proxied using Audit Committee Size has a positive and significant effect on ROA. Meanwhile, only Government Ownership and Institutional Ownership negatively and significantly affect ROE, while Board of Directors Size, Independent Board of Commissioners Size, and Audit Committee Size do not affect ROE. In addition, with the moderating factor of inflation rate, the research findings show a significant negative relationship between Government Ownership to ROA, Institutional Ownership to ROA and ROE, and Audit Committee Size to ROE. Meanwhile, with the moderating factor of inflation rate, only the size of the Independent Board of Commissioners positively and significantly affects ROE while the Size of the Board of Directors, Independent Board of Commissioners, and Audit Committee do not affect ROA. The same results for Government Ownership and Board of Directors Size also do not affect ROE with the moderating factor of inflation rate. This study provides information to management on how to run every business process in SOEs to implement good corporate governance, so that SOEs can maintain and improve financial performance even in unstable macroeconomic conditions. Good corporate governance practices can increase the liquidity and value of SOEs shares in the capital market. Investors will tend to invest in companies whose shares are liquid and whose value increases over time. Good corporate governance creates a positive perception in the market, which can boost stock prices. SOEs with strong corporate governance tend to have a more stable and reliable dividend policy. Investors seeking a steady income from their investments will be attracted to SOEs that are able to consistently provide dividends, even in uncertain economic conditions due to inflation. The results of this study provide input to the Government to be able to formulate more targeted policies to support the strengthening of corporate governance in SOEs that include stricter regulations, better supervision, and incentives for SOEs that implement good corporate governance. The Government needs to continue to encourage the improvement of corporate governance in SOEs as part of a long-term strategy to ensure stable and sustainable financial performance, even in economic conditions affected by inflation.